A Novel Figure-Eight Taping Technique for Managing Anterior Shoulder Instability in a Recreational Pitcher: A Case Report - Masashi Kawabata; Toru Miyata; Kazuma Miyatake (International Journal of Sports Physical Therapy)
# Background and Purpose